The Competitive Strategy of Shredded Fish Business in Abonindi Kendari - Agnes Amelia Layuk; Azhar Bafadal; Munirwan Zani (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
Abonindi is one of the businesses that process fish into shredded fish. Making shredded fish is relatively easy, so sliced fish can be processed on a small business scale—the potential results in business actors working on the identical product type on the market. Still, Abonindi's business does not affect the number of competitors at the producer-actor level. This makes researchers want to know how Abonindi's competitive strategy is in doing business. So this study aims to determine the internal and external factors of the Abonindi shredded fish business and formulate a competitive plan that is applied to the Abonindi shredded fish business. This research was conducted in the Benu-Benua Village, West Kendari District, Kendari City, from July 2021 to October 2022. This research used descriptive analysis and SWOT analysis. The research method used was a case study on the shredded Abonindi business. The variables for this research consist of the identity of the respondents, including age, education level, business experience, and number of family dependents. Internal factors include business strengths and weaknesses, and external factors include business opportunities and threats. Based on the results of the study shows that (a) internal factors, consisting of three strength factors, namely own business capital, adequate production technology and good use of promotional media, and two weak factors, namely product prices which are relatively high compared to competitors, type or variant of shredded fish is still small. (b) external factors, consisting of three opportunity factors, namely the existence of support from the government, strategic marketing locations, and expanding market demand, and four threat factors, namely fluctuating raw material costs, many similar businesses, uncertain climatic conditions, and the nature of perishable raw materials. Based on the SWOT analysis results, the strategy used in the Abonindi shredded fish business is quadrant I (one), namely the SO strategy (Strengths – Opportunities). SO strategy is a strategy that uses strengths to take advantage of opportunities. The SO strategy used is to utilise promotional media to market shredded products, with an expanding market demand to increase or expand the need for the Abonindi business.